1998
DOI: 10.1126/science.282.5390.897
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Structures with Three-Dimensional Periodicity at Optical Wavelengths

Abstract: Porous carbons that are three-dimensionally periodic on the scale of optical wavelengths were made by a synthesis route resembling the geological formation of natural opal. Porous silica opal crystals were sintered to form an intersphere interface through which the silica was removed after infiltration with carbon or a carbon precursor. The resulting porous carbons had different structures depending on synthesis conditions. Both diamond and glassy carbon inverse opals resulted from volume filling. Graphite inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
566
1
15

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,050 publications
(591 citation statements)
references
References 21 publications
9
566
1
15
Order By: Relevance
“…2c, Supplementary Figs 1 and 2, and Supplementary Movie 1). Unlike typical synthetic photonic crystals that often rely on crystalline arrays or multilayer thin films 33,34 , the coloured regions of our self-templated materials were found to be composed of quasi-ordered fibre bundles that are remarkably similar to the collagen fibre bundles found in structurally coloured avian and mammalian skins 10,11 . Atomic force microscopy (AFM) and fast Fourier transform (FFT) analyses showed that the observed colours are attributable to coherent scattering from the fibre bundle structures (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…2c, Supplementary Figs 1 and 2, and Supplementary Movie 1). Unlike typical synthetic photonic crystals that often rely on crystalline arrays or multilayer thin films 33,34 , the coloured regions of our self-templated materials were found to be composed of quasi-ordered fibre bundles that are remarkably similar to the collagen fibre bundles found in structurally coloured avian and mammalian skins 10,11 . Atomic force microscopy (AFM) and fast Fourier transform (FFT) analyses showed that the observed colours are attributable to coherent scattering from the fibre bundle structures (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Ordered self-assembly of hollow structures of silica [26], carbon [27] and titania [28,29] has drawn much attention recently because of their applications in lowloss dielectrics, catalysis, filtering and photonics. The low density of the material results in very low dielectric constant, which is a candidate for low-loss electronic devices.…”
Section: Mesoporous Materials For Low-loss Dielectrics and Catalysismentioning
confidence: 99%
“…Many methods have been demonstrated to form photonic bandgaps, such as lithographic and etching techniques 10 , spontaneous self-assembly of colloids 11 , synthetic opals [12][13][14] , inverted opals 15,16 and block copolymers [17][18][19][20][21] , each having their own characteristic advantages and drawbacks. The aim of this work is to demonstrate responsive photonic bandgaps in the solid state based on self-assembly of block copolymers, where temperature changes cause pronounced and reversible switching, which manifests itself, for example, as distinct colour changes.…”
mentioning
confidence: 99%